1991
DOI: 10.2307/2534790
|View full text |Cite
|
Sign up to set email alerts
|

Patent Expiration, Entry, and Competition in the U.S. Pharmaceutical Industry

Abstract: THE ETHICAL PHARMACEUTICAL industry is an important one, not so much for its economic size as for the benefits that it delivers to users of its products. The industry has been transformed structurally since the 1940s from a producer of selected chemicals to a research-oriented sector that makes a major contribution to the technology of health care. I Its very success in generating a stream of new drugs with important therapeutic benefits has involved the industry in intense public policy debates over the finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
315
0
11

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(342 citation statements)
references
References 20 publications
12
315
0
11
Order By: Relevance
“…This may happen, e.g., due to shifts in demand, the introduction of new production or distribution technologies, or market exit and entry. Even the threat of new market entry might trigger incumbents to increase patenting, since patents may work as market entry barriers (Bain, 1956;Caves, 1974;Caves et al, 1991;Porter, 1980;Rabino and Enayati, 1995).…”
Section: Changes In the Benefits Of Patentsmentioning
confidence: 99%
“…This may happen, e.g., due to shifts in demand, the introduction of new production or distribution technologies, or market exit and entry. Even the threat of new market entry might trigger incumbents to increase patenting, since patents may work as market entry barriers (Bain, 1956;Caves, 1974;Caves et al, 1991;Porter, 1980;Rabino and Enayati, 1995).…”
Section: Changes In the Benefits Of Patentsmentioning
confidence: 99%
“…We assume that profit margins range from the high margins enjoyed by producers of on-patent pharmaceuticals, to the lower margins enjoyed by hospitals. For drugs, Caves et al (1991), Grabowski and Vernon (1992) and Berndt, Cockburn, and Griliches (1996) estimate that producer variable costs are 20% of sales. On the other hand, Gaynor and Vogt (2003) find that hospitals have profit margins of 25%.…”
Section: Aggregate Consumer and Producer Surplusesmentioning
confidence: 99%
“…If on one hand this article describes the pattern of entry of generic drug suppliers into Brazil after the arrival of the first generic manufacturer in the Brazilian market, thus supporting the identification strategies used by Caves et al (1991), and Arvate et al (2013), on the other hand it contains some limitations. First, it does not allow for it to be identified how characteristics of the Brazilian market (such as income, population size, epidemiological and sanitary conditions, and other characteristics described in Morton (1997) and Kyle (2006)) affect the pattern of entry of generic drugs into Brazil.…”
Section: Introductionmentioning
confidence: 54%
“…Such studies implicitly assume that there is a continuous entry of generic drugs after their patent expiry, thus increasing the chance of generic suppliers entering into a public tender. However, no study prior to this article has sought to investigate whether this relationship suggested by Caves et al (1991), and Arvate et al (2013), is verified empirically. This article seeks to fill this gap in the literature.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation